2022
DOI: 10.3389/fimmu.2022.1062136
|View full text |Cite
|
Sign up to set email alerts
|

Predictive model for BNT162b2 vaccine response in cancer patients based on blood cytokines and growth factors

Abstract: BackgroundPatients with cancer, especially hematological cancer, are at increased risk for breakthrough COVID-19 infection. So far, a predictive biomarker that can assess compromised vaccine-induced anti-SARS-CoV-2 immunity in cancer patients has not been proposed.MethodsWe employed machine learning approaches to identify a biomarker signature based on blood cytokines, chemokines, and immune- and non-immune-related growth factors linked to vaccine immunogenicity in 199 cancer patients receiving the BNT162b2 va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Previous research had revealed an increase in IP-10 levels after vaccinations ( Tang et al., 2023 ), and the increase was evident in healthy individuals as well as in elderly or cancer patients after administration of the BNT162b2 vaccine ( Konnova et al., 2022 ). According to the literature, after receiving a second vaccine dose, a memory response was induced, leading to a significant increase in levels of IFN-g, IP-10/CXCL10, IL-6, and TNF-a that were crucial for quickly recruiting and activating effector immune cells ( Bergamaschi et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research had revealed an increase in IP-10 levels after vaccinations ( Tang et al., 2023 ), and the increase was evident in healthy individuals as well as in elderly or cancer patients after administration of the BNT162b2 vaccine ( Konnova et al., 2022 ). According to the literature, after receiving a second vaccine dose, a memory response was induced, leading to a significant increase in levels of IFN-g, IP-10/CXCL10, IL-6, and TNF-a that were crucial for quickly recruiting and activating effector immune cells ( Bergamaschi et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%